Perbandingan Penafsiran Ayat-Ayat Lingkungan dan Sains - Ahmed Hafiz Al Fikri; Pathur Rahman (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study aims to compare the interpretation of environmental and scientific verses in the Quran. This study uses a literature study approach. The results show that a comparison between environmental and scientific verses in the Quran demonstrates a complementary relationship. Scientific verses (kawniyah) reveal signs of God's greatness through the creation of nature, which encourages humans to think and research. Environmental verses (tasyri'iyah) provide an ethical and moral foundation for humans as caliphs to protect and preserve nature. The integration of the two produces a holistic understanding: scientific knowledge of nature should strengthen ethical awareness to protect it, not become a tool for its exploitation. A comparison of interpretations from various commentators, both classical and modern, proves that the Quran is a book that is timelessly relevant, able to adapt to scientific advances without losing its spiritual and ethical values.